Gulls (laridae) as bioindicators of flame retardant emissions from landfill: a species-assemblage investigation - Tongue, Andrew (2020)
The contamination of free-living avifauna via chemical pollution resulting from anthropogenic activity is globally ubiquitous and poses a threat for avian conservation. Waste streams are important reservoirs of several persistent organic pollutants (POPs), including legacy brominated flame retardants (BFRs). However, landfill is often an important foraging substrate for birds such as gulls (Laridae). Some BFRs are known to exert deleterious effects on birds. Given that lipophilic pollutants sequester in the yolk compartment of avian eggs, this tissue can be an important non-invasive biomonitoring matrix. The primary aim of this thesis was to assess whether gulls breeding in proximity to a UK landfill constitute effective bioindicators of BFR emissions, with an additional aim being the identification of a suitable bioindicator species for future biomonitoring purposes. Polybrominated diphenyl ethers (PBDEs) were detected in substantial concentrations (up to 7,000 ng/g lipid weight) in the eggs of five larid taxa of UK / European conservation concern (black-headed gulls Chroicocephalus ridibundus, common gulls Larus canus, great black-backed gulls L. marinus, European herring gulls L. argentatus and lesser black-backed gulls L. fuscus) breeding in proximity to a municipal solid waste landfill compared to reference conspecifics breeding away from landfill. Mean ∑8 PBDE concentrations in the eggs of landfill-breeding gulls followed lesser black-backed gulls > great black-backed gulls > herring gulls > common gulls > black-headed gulls. The novel brominated flame retardant, DBDPE, was detected in the highest concentrations reported in biota to date globally in the eggs of landfill-breeding great black-backed gulls and herring gulls (up to 8,000 ng/g lw) but was not detected in reference eggs. Given their numerical superiority at the landfill and colonies, the most statistically robust data was obtained for herring gulls. The eggs of landfill-breeding herring gulls exhibited significantly higher burdens of ...